The Implementation of Good Faith Principles in Online Sale and Purchase - W Widaningsih (Kertha Wicaksana, 2019)
Good faith is a basic principle in conducting a sale and purchase agreement. The activity of proceeding financial transaction in advance to receiving a purchased goods in a sale and purchase activity can be done online without the presence of both the customer and the seller in a face to face meeting or without first making physical verification on the goods to be purchased by the customer. In Indonesian such phenomenon dominates the online marketing activity and it is protected by the law with the term of good faith principles that must be applied in making a purchase agreement. The issue addressed in the present study is to highlight the important role of the online sale and purchase agreement and the legal consequences resulted from breaking the rules on it. The basic applicable law regulation on e-commerce in Indonesian is the one prescribed in the Civil Code, that is in the Law Number 8 of 1999 concerning Consumer Protection (Indonesian term is UUPK) and the Law Number 19 Year 2016 Law Number 11 Year 2008 concerning Information and Electronic Transactions (the Indonesian term is UU ITE). To achieve the objectives of the study, normative research approach is applied in analyzing the data. The results showed that the application of the principle of good faith in electronic commerce was realized by the existence of true and honest information by the parties who transacted, in this case the seller of a particular product offering a product of goods or services provided information about the actual condition of the goods without guile, does not provide misleading information while buyers who use or buy goods and or services used fulfill their obligations, namely making payments. Violations of good faith in the agreement can be criminalized according to the provisions of Article 62 UUPK and aggravated by the provisions of article 45 paragraph (2) of the ITE Law. The implementation of the principle of good faith in the online sale and purchase agreement covers all stages of the agreement, namely the pre-agreement stage, the agreement phase, and the post-agreement stage. Keyword: Good Faith Principle, Online Sale and Purchase Agreement